PERAN PBB SEBAGAI ORGANISASI INTERNASIONAL DALAM MENYELESAIKAN SENGKETA YURISDIKSI NEGARA ANGGOTANYA DALAM KASUS STATE IMMUNITY ANTARA JERMAN DENGAN ITALIA TERKAIT KEJAHATAN PERANG NAZI - Marupa Hasudungan Sianturi; Arif Arif; Jelly Leviza (Journal of USU International Law, 2014)
Abstract The United Nations is the biggest international organization in the history of the cooperation growth for many international living sector to all nations in this world. In the international people association, states often get difference of interest so that it can cause a dispute or conflict of state. The existence of the United Nations can take effective in solving international disputes that occur among all nations including in solving the state jurisdiction dispute in the state immunity case between Germany and Italy. The United Nations has the International Court of Justice as the principal judicial organ of the United Nations. International Court of Justice has the competence of the court and legal binding in settle the international disputes based on the United Nations principle. The United Nations has the function through the International Court of Justice in solving the state immunity case between Germany and Italy. The method used in this research is library research data collection. The competence of the International Court of Justice based on the agreement of the state. The legal binding of the International Court of Justice Judgement in deciding international disputes only bind to the parties in case. In addition, the International Court of Justice still effort to settle the case of state immunity between Germany and Italy in peace through the system of Judicial Settlement. Keyword : The United Nations, International Court of Justice, State Immunity